Knowledge mapping of COVID-19 and dentistry: A bibliometric analysis - Chen, Jia; Zhang, Qian; Liu, Xin; Han, Ying; Gong, Qiming (Frontiers in Public Health, 2023)
Background COVID-19 has a significant impact on dental medicine. The present study aims to overview dental-related research on COVID-19 by visual mapping method. Methods We analyzed the publications in the “Dentistry Oral Surgery Medicine” category in the Web of Science core collection. On June 10, 2022, we conducted an advanced search using the items TS = (“Novel coronavirus 2019” or “COVID 19” or “Coronavirus disease 2019” or “2019-nCOV” or “SARS-CoV-2” or “coronavirus-2”) and WC = (“Dentistry Oral Surgery medicine”) to screen publications in the dental field that focus on COVID-19 or SARS-CoV-2. The contributions of authors, journals, institutions, and countries were described using Microsoft Excel 2010 and VOSviewer. The keywords co-occurring analysis and references analysis were visualized using VOSviewer and CiteSpace. Results A total of 1,732 papers were identified between 2020 and 2022. The United States, the United Kingdom, and Brazil were three major contributors to this field. Univ São Paulo (Brazil) ranked first with 55 publications in this field. Martelli Junior, Hercilio from Universidade Jose do Rosario Vellano (Brazil) was the most prolific author with 19 publications. Oral Diseases and British Dental Journal were the two most productive journals. The central topics were dental practice and infection control, oral manifestation related to COVID-19, dental education and online learning, teledentistry, and mental health problems. Conclusion The growth rate of publications regarding dental research on COVID-19 has risen sharply. Research topics shifted from “Dental practice and infection control, oral manifestation related to COVID-19” in 2020 to “Dental education and online learning, teledentistry, mental health problems,” which are three important research topics for the future.